Método monoscópico para a determinação automática da altura de edifícios em fotografias aéreas - Demarqui, Edgar Nogueira [UNESP]; Hasegawa, Júlio Kiyoshi [UNESP]; Galo, Mauricio [UNESP] (My University, 2008)
This paper proposes a monoscopic method for automatic determination of building's heights in digital photographs areas, based on radial displacement of points in the plan image and geometry at the time the photo is obtained. Determination of the buildings' heights can be used to model the surface in urban areas, urban planning and management, among others. The proposed methodology employs a set of steps to detect arranged radially from the system of photogrammetric coordinates, which characterizes the lateral edges of buildings present in the photo. In a first stage is performed the reduction of the searching area through detection of shadows projected by buildings, generating sub-images of the areas around each of the detected shadow. Then, for each sub-image, the edges are automatically extracted, and tests of consistency are applied for it in order to be characterized as segments of straight arranged radially. Next, with the lateral edges selected and the knowledge of the flight height, the buildings' heights can be calculated. The experimental results obtained with real images showed that the proposed approach is suitable to perform the automatic identification of the buildings height in digital images.
Monoscopic method for the automatic determination of height of buildings in air photos
Keywords: Height of buildings; Relief displacement; Shadows detection